The Integration of Natural Science and Theology in Tafsīr Al-Jawāhir: A Study of the Thought of Imam Ṭanṭāwī Jawharī - Zulfikar, Zaky Zimmatillah; Yolan Hardika Pratama; Moch Nur Syahrus Syahbana (Universitas Islam Negeri Raden Intan Lampung, 2025)
Abstract This study examines the integration between natural sciences and the science of tawḥīd in al-Jawāhir fī Tafsīr al-Qur’ān al-Karīm, the seminal Qur’anic exegesis of Imam Tantawi Jauhari. Using a qualitative approach through library research, this paper explores how Jauhari constructs an epistemological relationship between natural phenomena (āyāt kauniyyah) and divine unity (tawḥīd). The findings reveal that Jauhari views the universe as an interconnected and harmonious system (waḥdāniyyat al-‘ālam), reflecting the oneness and wisdom of the Creator (waḥdāniyyat al-wujūd). He asserts that observing and reflecting upon the universe constitutes a form of intellectual devotion that strengthens faith and deepens spiritual awareness of God’s majesty. Through his interpretive method, Jauhari not only bridges the Qur’an and modern science but also offers an integrative paradigm that unites reason, revelation, and the cosmic order within a single framework of tawḥīd. This study concludes that al-Jawāhir represents an epistemological model of Islamic knowledge, positioning scientific inquiry as a pathway to a deeper understanding of the Divine. Keywords: Imam Tantowi Jauhari; Integration of knowledge; Jawahir fi Tafsir al-Quran.